A legal review of the World Trade Organisation’s applications of the Agreement on Trade-Related Aspects of Intellectual Property Rights to ensure equitable access to health care during the COVID-19 pandemic - Carstens, Jan Paul (Stellenbosch : Stellenbosch University, 2023)
Thesis (LLM)--Stellenbosch University, 2023.